Determinan Pendapatan Asli Daerah Di Jawa Timur Pada Masa Covid-19 - Gupita Gustiarni; Amir Hidayatulloh (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The aim of the study was to analyze the determinants of regional original income in East Java during the Covid-19 period. The population of this study is all city/district APBD realization data in Indonesia in 2020. Meanwhile, the research sample is data on city/district APBD realization in East Java. The data analysis technique of this study used multiple linear regression analysis. This study obtained the results that local revenue in East Java during the Covid-19 period was influenced by restaurant taxes and hotel taxes. However, the entertainment taxes did not affect local revenue in East Java during the Covid-19 pandemic. This is because in 2020, cinemas will stop operating.